Neonatal complications in women with premature rupture of membranes (PROM) at term and near term and its correlation with time lapsed since PROM to delivery. (January 2020) - Gupta, Shruti; Malik, Sunita; Gupta, Shailesh
Premature rupture of membranes (PROM) is a common problem with controversies in its management. The aim of our study was to find out the prevalence of neonatal complications and their correlation with the latent period in babies born to mothers with PROM at 34–40 weeks of gestation. This prospective cohort study was performed on 200 pregnant women with PROM at or near term. After birth, neonates were screened for sepsis. Other outcome measures included birth asphyxia, stay in the Neonatal Intensive Care Unit (NICU) and neonatal mortality. These were correlated against time spent from PROM. Duration after which risk of neonatal sepsis increased immensely was calculated by ROC. The prevalence of specific neonatal complications was as follows: birth asphyxia (8%); neonatal sepsis (4%); NICU admission (26%); and neonatal mortality (2%). Complications increased with an increasing latent period. Beyond 37 h of latency, the rate of neonatal sepsis increases dramatically. In conclusion, pregnancies with PROM at and near term should not be managed expectantly. All neonates born after 37 h of latent PROM should be stringently evaluated for sepsis.